Sankofa: saberes e práticas de professores pedagogos para a educação das relações étnico-raciais em cursos de licenciatura em química do IFRN - Santos, Nadia Farias dos (2023)
An anti-racist education presupposes a formation that values the history, culture and identities of their peers, in a dialectical process established and designed for these diversities. The present research has as the object of study the relationship between knowledge and practices triggered by pedagogue teachers for the education and teaching of ethnic-racial relations, seeking to understand the performance of Pedagogy teachers in Chemistry undergraduate courses, concerning the teaching of this theme based on the principle of equal rights, recognition and appreciation of the Afro-Brazilian and African cultures and in the applicability of laws and guiding standards of a proposal of formation for a racial-inclusive education. And as a general objective, to analyze knowledge and practices of pedagogue teachers for the education of ethnic-racial relations of undergraduate courses in Chemistry of the Federal Institute of Education, Science and Technology of Rio Grande do Norte from the perspective of Afrocentricity. The specific objectives: to identify, in the Pedagogical Policy Projects of the Chemistry Degree Courses of IFRN, epistemological and theoretical-methodological foundations afro-centered in the context of ethnic-racial relations; to list the afro-centered knowledge and practices mobilized in the teaching practice of pedagogue teachers regarding the education of ethnic-racial relations and to understand the interfaces and relations in the Chemistry Degree courses of IFRN and the role of education of ethnic-racial relations. The research was developed with teachers graduated in Pedagogy who teach in chemistry courses. The data were collected through online questionnaires, interviews and Political Pedagogical Projects of the courses, which were analyzed based on Bardin’s content analysis and anchored in Asante’s theory of Afrocentricity, using three categories of analysis: awareness, location and agencies, central concepts of the theoretical perspective adopted. From the data, it was possible to identify that the contents of Afro-Brazilian, African and Indigenous History and Culture are treated superficially or non-existent, revealing the absence of African and Afro-diasporic centrality in the curricula. The research also revealed that these absences occur as a reflection of the training of the teachers and the non-compliance with the obligation of Laws 10.639/03 and 11.645/08, leaving the responsibility to the teachers or under the responsibility of the Center for Studies of History and Afro-Brazilian, African and Indigenous Culture. Another conclusion of this study is the unpreparedness of teachers to work on the subject and also that there is little or no participation in training in graduation, and continuing education and point out this condition as a justification for the difficulties of working the theme more forcefully in their classrooms.